The perceived COVID-19 pandemic risk and mental distress in China: the mediating role of interpersonal trust and the moderating role of social cohesion - Zhou, Hao; Liu, Xiangqian; Wu, Jing; Liao, Chuanjing; Zhao, Shengyu (Frontiers in Psychology, 2025)
IntroductionAn increasing number of studies have highlighted the consequences of the coronavirus disease 2019 (COVID-19) pandemic and the mechanisms through which it inflicts harm. However, few have examined the relationship between perceived pandemic risk and mental distress from an interpersonal perspective. Drawing on the stress system model, trust theory, social-support theory, and exchange–emotion–cohesion theory, the present study investigates whether perceived pandemic risk is positively associated with mental distress, whether different types of interpersonal trust mediate this relationship, and whether social cohesion moderates this mediating process.MethodsThe theoretical model was tested using data from 18,278 Chinese residents (Mage = 32.63 years, standard deviation = 13.85) between March and June 2020. Participants in this cross-sectional study completed a named survey assessing their perceived pandemic risk, different types of interpersonal trust, mental distress, and social cohesion. Correlational and moderated mediation analyses examined how perceived risk relates to mental distress via interpersonal trust, while estimating social cohesion’s moderated role in this pathway.ResultsPerceived pandemic risk was positively associated with mental distress. Interpersonal trust among non-strangers (family, friends and colleagues) partially mediated this link, and social cohesion moderated the trust-to-distress pathway specifically for friends and colleagues trust. In contexts of lower social cohesion, the indirect effect through friends and colleagues trust was stronger, indicating greater vulnerability to mental distress.DiscussionThese findings extend research on pandemic-related mental distress by identifying acquaintance trust in ordinary friends and colleagues as a key interpersonal mechanism and demonstrating that cohesive community contexts can buffer the psychological consequences of eroded trust. Practitioners should consider leveraging social relationships in public-health crisis responses.